Trans-perovskite solar module based on post-treatment passivation and preparation method thereof

By using 7-ethylcamptothecin on the surface of perovskite film for post-treatment, the problems of surface defects of perovskite film and non-radiative recombination at the interface are solved, the photoelectric conversion efficiency of perovskite solar modules is improved, and its commercial application is promoted.

CN120548009APending Publication Date: 2025-08-26GUANGDONG BENSHU LIGHT ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510707785.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-29
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

In the existing trans perovskite solar modules, there are many surface defects in the perovskite film and the non-radiative recombination at the interface between the perovskite layer and the adjacent electron transport layer are severe, which affects the photoelectric conversion efficiency, and the problem is more prominent in large-area modules.

Method used

7-ethylcamptothecin is used as the surface defect passivation layer, and a high-quality perovskite solar module is prepared by post-treatment on the surface of the perovskite film, optimizing the interface between the perovskite layer and the electron transport layer, reducing defect states, and improving interface energy level matching.

Benefits of technology

Significantly reduce the defect density of perovskite films, improve open circuit voltage and fill factor, enhance photoelectric conversion efficiency, and promote the commercialization of perovskite solar modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120548009A_ABST
    Figure CN120548009A_ABST
Patent Text Reader

Abstract

The invention discloses a trans-perovskite solar module and a preparation method thereof. The trans-perovskite solar module is composed of a transparent conductive substrate, a hole transport layer, an organic-inorganic hybrid metal halide perovskite light absorption layer, a surface defect passivation layer, an electron transport layer and a metal electrode. Wherein the surface defect passivation layer is made of 7-ethyl camptothecin. A 7-ethyl camptothecin solution is adopted to carry out post-treatment on the perovskite photoactive layer or the perovskite / C60 interface, so that perovskite crystallization is improved, and preferred growth of crystal grains is promoted; the defects of the perovskite thin film are passivated, and non-radiative recombination is reduced; the open-circuit voltage and the filling are obviously improved, and finally higher photoelectric conversion efficiency is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cells, and in particular relates to an inverse perovskite solar module based on post-processing passivation and a preparation method thereof. Background Art

[0002] Lead-based halide perovskite solar cells (PSCs) have attracted considerable attention due to their excellent optoelectronic properties, low-cost raw materials, scalable fabrication techniques, and low-temperature manufacturing processes. After more than a decade of development, the power conversion efficiency of single-junction, small-area PSCs has increased from an initial 3.8% to a staggering 27%. Large-area module efficiencies have also significantly improved, attracting widespread attention from both academia and the photovoltaic industry. Within the next few years, they are expected to replace traditional silicon solar cells and become one of the most cost-effective photovoltaic technologies. Currently, high-efficiency inverse perovskite solar cells commonly use polycrystalline perovskite films as the light-absorbing layer. However, polycrystalline perovskite films prepared by solution methods are prone to forming high-density defects during the crystallization process, including intrinsic point defects (such as halogen vacancies and lead interstitials), grain boundary defects, surface defects, and lead clusters. These defect states act as nonradiative recombination centers, exacerbating carrier recombination and inducing ion migration, severely limiting the device's power conversion efficiency. In particular, as module area increases, nonradiative recombination losses of photogenerated carriers and surface defects in the film become more prominent.

[0003] Therefore, there is an urgent need to introduce effective post-treatment to passivate the trap states on the surface of the perovskite film, modify the interface on the perovskite layer, and adjust the interface energy levels for better matching, so as to prepare high-efficiency inverse perovskite solar modules. Summary of the Invention

[0004] In response to the problems of existing inverse perovskite solar modules, such as the large number of surface defects in the perovskite film and the high non-radiative recombination at the interface between the perovskite layer and the adjacent electron transport layer, the present invention discloses a method for preparing a high-efficiency inverse perovskite solar module using a novel surface defect passivation layer. By post-treating the perovskite film surface with 7-ethylcamptothecin, a perovskite solar module with higher film quality and better photoelectric conversion efficiency can be prepared.

[0005] In order to achieve the above purpose, the technical solutions adopted are as follows: An inverse perovskite solar module, as shown in the attached Figure 6 As shown, it consists of a transparent conductive substrate 1, a hole transport layer 2, an organic-inorganic hybrid metal halide perovskite light absorption layer 3, a surface defect passivation layer 4, a metal fluoride layer 5, an electron transport layer 6 and a metal electrode 7.

[0006] The surface defect passivation layer is 7-ethylcamptothecin with a concentration of 0.25-1 mg / mL.

[0007] According to the above solution, the transparent conductive substrate is one of ITO conductive glass and FTO conductive glass.

[0008] According to the above scheme, the hole transport layer is nickel oxide (NiO X ) nanoparticles and self-assembled monolayers (SAMs) or a combination of both.

[0009] According to the above scheme, the organic-inorganic hybrid metal halide perovskite light absorbing layer is Cs X FA Y MA 1-X-Y PbI3 (where 0≤X≤0.05, 0.70≤Y≤0.90), with a thickness of 400~700 nm.

[0010] According to the above solution, the surface defect passivation layer is 7-ethylcamptothecin.

[0011] According to the above scheme, the electron transport layer is a fullerene derivative and tin dioxide, with thicknesses of 20-30 nm and 20-30 nm respectively.

[0012] According to the above scheme, the metal electrode is one of Ag, Cu, and Au, and has a thickness of 80-100 nm.

[0013] The method for preparing the above-mentioned inverse perovskite solar module comprises the following steps: 1) For 5×5 cm 2 The transparent conductive substrate is cleaned; laser P1 scribing is performed; and a hole transport layer is prepared.

[0014] 2) Cs X FA Y MA 1-X-Y PbI3 perovskite precursor powder was dissolved in a mixed solvent of N, N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), and the organic-inorganic hybrid metal halide perovskite light-absorbing layer was prepared by spin coating.

[0015] 3) 7-Ethylcamptothecin powder was dissolved in isopropyl alcohol (IPA) solvent and a surface defect passivation layer was prepared by spin coating.

[0016] 4) Prepare the electron transport layer; perform laser P2 scribing.

[0017] 5) Prepare metal electrodes; perform laser P3 scribing and laser P4 edge cleaning.

[0018] According to the above scheme, the precursor powder in step 2 includes: CsI, FAI, MACl, PbI2; the volume ratio of DMF and DMSO is (3.5-4.5):1, and the concentration of the perovskite precursor solution is 1.2-1.8 mmol / mL.

[0019] According to the above scheme, step 2 also includes using chlorobenzene as an anti-solvent to assist film formation, using a two-stage spin coating method, with the first stage speed being 1000-2000 rpm and the time being 5-10 s, and the second stage speed being 4000-5000 rpm and the time being 30-40 s, and 300-500 μL of chlorobenzene being added dropwise in the penultimate 15-20 s of the second stage; the spin coating process temperature is 18-24°C; and annealing is performed at 100°C for 30-60 min.

[0020] According to the above scheme, step 3 also includes using a dynamic spin coating method with a rotation speed of 4000-6000 rpm for 40-50 seconds, adding 60-80 μL of 7-ethylcamptothecin solution dissolved in IPA in the first 10-20 seconds; the spin coating process temperature is 18-24°C; and annealing is performed at 100°C for 5-15 minutes.

[0021] The beneficial technical effects of the present invention are as follows: 1) The grain size of the perovskite film prepared by the present invention is significantly increased, and the grain arrangement is denser; the defect density of the optimized perovskite film is significantly reduced compared with the untreated film, effectively suppressing the non-radiative recombination of carriers.

[0022] 2) The perovskite solar module prepared by the present invention has higher open-circuit voltage and fill factor, and significantly improved photoelectric conversion efficiency. The present invention will effectively promote the commercialization process of perovskite solar modules. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the Fourier infrared spectrum of 7-ethylcamptotheca and lead iodide.

[0024] Figure 2 2 are the XRD patterns of the perovskite films of Comparative Example 1 and Example 1.

[0025] Figure 3 These are SEM images of the perovskite film surfaces of Comparative Example 1 and Example 1.

[0026] Figure 4 SCLC diagrams of the perovskite solar cells of Comparative Example 1 and Example 1.

[0027] Figure 5 1 is a comparison diagram of the JV curves of the perovskite solar modules of Comparative Example 1 and Example 1 of the present invention.

[0028] Figure 6 Schematic diagram of the structure of the inverse perovskite solar module in the present invention. DETAILED DESCRIPTION

[0029] The following examples further illustrate the technical solutions of the present invention but are not intended to limit the scope of protection of the present invention.

[0030] The specific embodiment provides an inverse perovskite solar module, as shown in the attached Figure 6 As shown, it consists of a transparent conductive substrate 1, a hole transport layer 2, an organic-inorganic hybrid metal halide perovskite light absorption layer 3, a surface defect passivation layer 4, a metal fluoride layer 5, an electron transport layer 6 and a metal electrode 7.

[0031] The surface defect passivation layer is 7-ethylcamptothecin with a concentration of 0.25-1 mg / mL.

[0032] The specific embodiment also provides a method for preparing the above-mentioned inverse perovskite solar module, comprising the following steps: 1) For 5×5 cm 2 Cleaning the transparent conductive substrate; performing laser P1 scribing; and preparing a hole transport layer. 2) Cs X FA Y MA 1-X-Y PbI3 perovskite precursor powder was dissolved in a mixed solvent of N, N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), and the organic-inorganic hybrid metal halide perovskite light-absorbing layer was prepared by spin coating.

[0033] 3) 7-Ethylcamptothecin powder was dissolved in isopropyl alcohol (IPA) solvent and a surface defect passivation layer was prepared by spin coating.

[0034] 4) Prepare electron transport layer; perform laser P2 scribing; 5) Prepare metal electrodes; perform laser P3 scribing and laser P4 edge cleaning.

[0035] In the optimized protocol, step 2 also includes the use of chlorobenzene as an antisolvent to assist film formation. A two-stage spin coating process is employed: the first stage is at a speed of 1000-2000 rpm for 5-10 seconds, and the second stage is at a speed of 4000-5000 rpm for 30-40 seconds. 300-500 μL of chlorobenzene is added dropwise in the 15-20 seconds before the second stage. The spin coating process is performed at a temperature of 20-24°C, and the film is annealed at 100°C for 50-80 minutes. Step 3 also includes dynamic spin coating at a speed of 4000-6000 rpm for 40-50 seconds. In the 10-20 seconds before the second stage, 60-80 μL of a solution of 7-ethylcamptothecin in IPA is added dropwise. The spin coating process is performed at a temperature of 18-24°C, and the film is annealed at 100°C for 5-15 minutes.

[0036] The present invention is further explained below by more specific examples, but does not constitute any limitation.

[0037] The main raw materials used in the following examples are from the following sources: NiO X Nanoparticles were purchased from Youxuan Technology Company, and polycarbazole phosphate (Poly-4PACz) powder, 7-ethylcamptothecin, CsI, MACl, FAI, PbI2, C60 and SnO2 were purchased from Xi'an Baolait Company.

[0038] The main test methods involved in the following examples are as follows: Fourier transform infrared spectroscopy (FTIR) was measured by Nicolet 6700. The crystal structure characterization of the perovskite film was completed by X-ray diffraction (XRD) technology, and the test was carried out on a D8 Advance X-ray diffractometer equipped with a Cu Kα radiation source. The morphology of the film was measured by SEM (JEOL, JSM-7500F, 104 Japan) at an accelerating voltage of 5.0 KV. In the spatial confinement current (SCLC) test, FTO / hole transport layer / perovskite absorption layer / electron transport layer / Ag pure electronic structure devices were prepared to measure the current-voltage change curves of different devices in the dark state. The defect filling limit voltage ( V TFL ). The defect state density of the film is calculated according to the following formula: n trap = 2εε0 V TFL / eL 2 Here, ε, ε0, and e represent the relative dielectric constant, vacuum dielectric constant, and elementary charge of the perovskite, respectively, and L represents the thickness of the perovskite layer.

[0039] Current density-voltage ( JV ) was characterized using a steady-state solar cell module simulator. The lighting current was measured under simulated sunlight (Zhongsen Electric Power Co., Ltd., 100 mW / cm 2 and AM 1.5 G irradiation). The reverse sweep range was 25 V to 0 V, and 400 data points were collected. Example 1

[0040] 1) Ultrasonic cleaning of the etched FTO conductive substrate was performed with deionized water, acetone, and anhydrous ethanol in sequence, with each cleaning time lasting 15 minutes. 2) The cleaned FTO conductive substrate was laser-scribed with P1, treated with UVO for 20 min, and then spin-coated with 10 mg / mL NiO X Nanoparticles aqueous solution and 0.5 mg / mL polycarbazole phosphate (Poly-4PACz) solution.

[0041] 3) Weigh Cs 0.05 MA 0.05 FA 0.90 PbI3 perovskite precursor powder was dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO). The molar ratio of CsI to FAI was 5:90, the molar ratio of MACl to FAI was 5:90, and the molar ratio of PbI2 to FAI was 10:9. The volume ratio of DMF to DMSO was 4:1, and the concentration of the perovskite precursor solution was 1.5 mmol / mL.

[0042] The obtained precursor solution was evenly spread on the FTO substrate treated with Poly-4PACz, and chlorobenzene was used as an anti-solvent to assist film formation. A two-stage spin coating method was used, with a first-stage speed of 2000 rpm and a time of 10 s, and a second-stage speed of 4000 rpm and a time of 40 s. 300 μL of chlorobenzene was added at the 20th second before the end of the second stage.

[0043] The obtained perovskite film was annealed at 100 °C for 30 min.

[0044] 4) Post-treatment of the annealed perovskite film: spin-drip 0.25 mg / mL 7-ethylcamptothecin solution onto the spin-coated perovskite film at 5000 rpm for 40 s. After 10 s, add 80 μL of 7-ethylcamptothecin solution and anneal at 100°C for 5 min.

[0045] 5) The obtained perovskite film was evaporated with 25 nm of C60 and atomic layer deposited with 20 nm of SnO2, and then laser P2 scribing was performed.

[0046] 6) Evaporate 100 nm of Cu, perform laser P3 scribing and laser P4 edge cleaning. Example 2

[0047] 1) Ultrasonic cleaning of the etched FTO conductive substrate was performed with deionized water, acetone, and anhydrous ethanol in sequence, with each cleaning time lasting 15 minutes. 2) The cleaned FTO conductive substrate was laser-scribed with P1, treated with UVO for 20 min, and then spin-coated with 10 mg / mL NiO X Nanoparticles aqueous solution and 0.5 mg / mL polycarbazole phosphate (Poly-4PACz) solution.

[0048] 3) Weigh Cs 0.05 MA 0.05 FA 0.90 PbI3 perovskite precursor powder was dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO). The molar ratio of CsI to FAI was 5:90, the molar ratio of MACl to FAI was 5:90, and the molar ratio of PbI2 to FAI was 10:9. The volume ratio of DMF to DMSO was 4:1, and the concentration of the perovskite precursor solution was 1.5 mmol / mL.

[0049] The obtained precursor solution was evenly spread on the FTO substrate treated with Poly-4PACz, and chlorobenzene was used as an anti-solvent to assist film formation. A two-stage spin coating method was used, with a first-stage speed of 2000 rpm and a time of 10 s, and a second-stage speed of 4000 rpm and a time of 40 s. 300 μL of chlorobenzene was added at the 20th second before the end of the second stage.

[0050] The obtained perovskite film was annealed at 100 °C for 30 min.

[0051] 4) Post-treatment of the annealed perovskite film: spin-drip 0.5 mg / mL 7-ethylcamptothecin solution onto the spin-coated perovskite film at 5000 rpm for 40 s. After 10 s, add 80 μL of 7-ethylcamptothecin solution and anneal at 100°C for 5 min.

[0052] 5) The obtained perovskite film was evaporated with 25 nm of C60 and atomic layer deposited with 20 nm of SnO2, and then laser P2 scribing was performed.

[0053] 6) Evaporate 100 nm of Cu, perform laser P3 scribing and laser P4 edge cleaning. Example 3

[0054] 1) Ultrasonic cleaning of the etched FTO conductive substrate was performed with deionized water, acetone, and anhydrous ethanol in sequence, with each cleaning time lasting 15 minutes. 2) The cleaned FTO conductive substrate was laser-scribed with P1, treated with UVO for 20 min, and then spin-coated with 10 mg / mL NiO X Nanoparticles aqueous solution and 0.5 mg / mL polycarbazole phosphate (Poly-4PACz) solution.

[0055] 3) Weigh Cs 0.05 MA 0.05 FA 0.90 PbI3 perovskite precursor powder was dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO). The molar ratio of CsI to FAI was 5:90, the molar ratio of MACl to FAI was 5:90, and the molar ratio of PbI2 to FAI was 10:9. The volume ratio of DMF to DMSO was 4:1, and the concentration of the perovskite precursor solution was 1.5 mmol / mL.

[0056] The obtained precursor solution was evenly spread on the FTO substrate treated with Poly-4PACz, and chlorobenzene was used as an anti-solvent to assist film formation. A two-stage spin coating method was used, with a first-stage speed of 2000 rpm and a time of 10 s, and a second-stage speed of 4000 rpm and a time of 40 s. 300 μL of chlorobenzene was added at the 20th second before the end of the second stage.

[0057] The obtained perovskite film was annealed at 100 °C for 30 min.

[0058] 4) Post-treatment of the annealed perovskite film: spin-drip 0.75 mg / mL 7-ethylcamptothecin solution onto the spin-coated perovskite film at 5000 rpm for 40 s. After 10 s, add 80 μL of 7-ethylcamptothecin solution and anneal at 100°C for 5 min.

[0059] 5) The obtained perovskite film was evaporated with 25 nm of C60 and atomic layer deposited with 20 nm of SnO2, and then laser P2 scribing was performed.

[0060] 6) Evaporate 100 nm of Cu, perform laser P3 scribing and laser P4 edge cleaning.

[0061] Comparative Example 1 1) Ultrasonic cleaning of the etched FTO conductive substrate was performed with deionized water, acetone, and anhydrous ethanol in sequence, with each cleaning time lasting 15 minutes. 2) The cleaned FTO conductive substrate was laser scribed with P1, treated with UVO for 20 min, and then spin-coated with 10 mg / mL NiO X Nanoparticles aqueous solution and 0.5 mg / mL polycarbazole phosphate (Poly-4PACz) solution.

[0062] 3) Weigh Cs 0.05 MA 0.05 FA 0.90 PbI3 perovskite precursor powder was dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO). The molar ratio of CsI to FAI was 5:90, the molar ratio of MACl to FAI was 5:90, and the molar ratio of PbI2 to FAI was 10:9. The volume ratio of DMF to DMSO was 4:1, and the concentration of the perovskite precursor solution was 1.5 mmol / mL.

[0063] The obtained precursor solution was evenly spread on the FTO substrate treated with Poly-4PACz, and chlorobenzene was used as an anti-solvent to assist film formation. A two-stage spin coating method was used, with a first-stage speed of 2000 rpm and a time of 10 s, and a second-stage speed of 4000 rpm and a time of 40 s. 300 μL of chlorobenzene was added at the 20th second before the end of the second stage.

[0064] The obtained perovskite film was annealed at 100 °C for 30 min.

[0065] 4) The obtained perovskite film was evaporated with 25 nm of C60 and atomic layer deposited with 20 nm of SnO2, and then P2 laser scribing was performed.

[0066] 5) Evaporate 100 nm of Cu, perform P3 laser scribing and P4 laser edge cleaning.

[0067] Table 1 shows the relevant parameters of the perovskite solar modules of the above embodiments and comparative examples.

[0068] Table 1 Device <![CDATA[V OC (V)]]> <![CDATA[J SC (mA / cm 2 )]]> FF (%) PCE (%) <![CDATA[R s (Oh)]]> <![CDATA[R sh (Oh)]]> Comparative Example 1 10.445 2.50 66.16 17.20 32.73 924.98 Example 1 11.000 2.50 71.03 19.55 25.57 937.37 Example 2 10.970 2.50 71.18 19.24 26.15 986.20 Example 3 10.966 2.52 67.98 18.81 23.59 986.22 Comparison of Fourier transform infrared spectra of mixed samples of lead iodide, 7-ethylcamptothecin and lead iodide is shown in the attached Figure 1 As shown, the characteristic peak position of the NH bond in the mixed sample shifted significantly, and the vibration enhancement of the C=O bond was observed, indicating that the C=O group formed a coordination effect with the uncoordinated Pb atoms in the perovskite lattice, effectively passivating the crystal defects.

[0069] The XRD diffraction patterns of the perovskite films of Comparative Example 1 and Example 1 are shown in the attached Figure 2As shown, no residual diffraction peak of PbI2 was detected in the sample of Example 1, and the intensity of the characteristic peak of the perovskite (110) crystal plane was relatively improved, indicating that 7-ethylcamptothecin improved crystallization through coordination and promoted preferential growth of grains.

[0070] The SEM images of the perovskite solar perovskite film surface of Comparative Example 1 and Example 1 are shown in the attached Figure 3 As shown, the average grain size of the perovskite light absorbing layer of Example 1 is increased, and the grains are arranged more closely, which effectively reduces the holes inside the light absorbing layer and improves the quality of the film.

[0071] The SCLC curves of the perovskite solar cell of Comparative Example 1 and Example 1 are shown in the attached Figure 4 As shown, the trap filling limit voltage of the perovskite solar cell in Example 1 is reduced, the surface defects of the film are significantly reduced, and the non-radiative recombination of carriers is effectively suppressed.

[0072] The JV curves of the perovskite solar modules of Comparative Example 1 and Example 1 are shown in the attached Figure 5 As shown, the open circuit voltage and fill factor of the perovskite solar module in Example 1 are significantly increased, ultimately achieving a higher photoelectric conversion efficiency.

[0073] The above-described embodiments merely illustrate several implementations of the present invention, and while their descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, all of which fall within the scope of protection of the present invention. Therefore, the scope of protection of the patent for this invention shall be determined by the appended claims.

Claims

1. An inverse perovskite solar module, characterized in that It consists of a transparent conductive substrate, a hole transport layer, an organic-inorganic hybrid metal halide perovskite light absorption layer, a surface defect passivation layer, an electron transport layer and a metal electrode; The surface defect passivation layer is 7-ethylcamptothecin with a concentration of 0.25-1 mg / mL.

2. The inverse perovskite solar module according to claim 1, characterized in that The transparent conductive substrate is one of ITO conductive glass and FTO conductive glass; the hole transport layer is nickel oxide (NiO X ) nanoparticles and self-assembled monolayers (SAMs) or a combination of both.

3. The inverse perovskite solar module according to claim 1, characterized in that The organic-inorganic hybrid metal halide perovskite light absorbing layer is Cs X FA Y MA 1-X-Y PbI3, where 0≤X≤0.05, 0.70≤Y≤0.90; thickness is 400~700 nm.

4. The inverse perovskite solar module according to claim 1, characterized in that The surface defect passivation layer is 7-ethylcamptothecin.

5. The inverse perovskite solar module according to claim 1, characterized in that The electron transport layer is a fullerene derivative and tin dioxide, and the thicknesses are 20-30 nm and 20-30 nm respectively.

6. The inverse perovskite solar module according to claim 1, characterized in that The metal electrode is one of Ag, Cu and Au, and has a thickness of 80-100 nm.

7. The method for preparing the inverse perovskite solar module according to claim 1, characterized in that The following steps are involved: 1) For 5×5 cm 2 Cleaning the transparent conductive substrate; performing laser P1 scribing; and preparing a hole transport layer. 2) Cs X FA Y MA 1-X-Y The PbI3 perovskite precursor powder was dissolved in a mixed solvent of N, N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), and the organic-inorganic hybrid metal halide perovskite light-absorbing layer was prepared by spin coating. 3) Dissolve 7-ethylcamptothecin powder in isopropyl alcohol (IPA) solvent and prepare a surface defect passivation layer by spin coating; 4) Prepare electron transport layer; perform laser P2 scribing; 5) Prepare metal electrodes; perform laser P3 scribing and laser P4 edge cleaning.

8. The method for preparing an inverse perovskite solar module according to claim 7, wherein The precursor powder in step 3 includes: CsI, FAI, MACl, PbI2; the volume ratio of DMF and DMSO is (3.5-4.5):1, and the concentration of the perovskite precursor solution is 1.2-1.8 mmol / mL.

9. The method for preparing an inverse perovskite solar module according to claim 7, wherein Step 2 also includes using chlorobenzene as an anti-solvent to assist film formation, using a two-stage spin coating method, with the first stage speed being 1000-2000 rpm and the time being 5-10 s, and the second stage speed being 4000-5000 rpm and the time being 30-40 s, and 300-500 μL of chlorobenzene being added dropwise in the penultimate 15-20 s of the second stage; the spin coating process temperature is 18-24°C; and annealing is performed at 100°C for 30-60 min.

10. The method for preparing an inverse perovskite solar module according to claim 7, wherein Step 3 also includes using a dynamic spin coating method with a rotation speed of 4000-6000 rpm for 40-50 seconds, adding 60-80 μL of 7-ethylcamptothecin solution dissolved in IPA in the first 10-20 seconds; the spin coating process temperature is 18-24° C.; and annealing at 100° C. for 5-15 minutes.